THE EFFECT OF BRAND IMAGE, PRODUCT QUALITY AND CONSUMER SATISFACTION ON CONSUMER LOYALTY (CASE STUDY OF BU WIDODO'S GUDEG RESTAURANT IN WIJILAN) - Putri Dwi Cahyani; Susanto Susanto; Nurullaila Nurullaila (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This study aims to analyze: the effect of Brand Image, Product Quality and Consumer Satisfaction simultaneously and significantly on Consumer Loyalty, the influence of Brand Image partially on Consumer Loyalty, the influence of Product Quality partially on Consumer Loyalty, the effect of partial Consumer Satisfaction on Consumer Loyalty at the Gudeg Bu Widodo Restaurant in Wijilan Yogyakarta. This study uses primary data using a questionnaire method distributed to 100 respondents from consumers of Warung Gudeg Bu Widodo in Wijilan. This study used a questionnaire data collection method with non-probability sampling/nonrandom sampling technique. This research uses Data Quality Test, Multiple Regression Test, F Test, t Test, Coefficient of Determination Test (R²). The results of this study indicate that Brand Image, Product Quality and Consumer Satisfaction simultaneously have a positive and significant effect on Consumer Loyalty. Brand Image partially has a positive and significant effect on Consumer Loyalty. Product quality partially has a positive and significant effect on Consumer Loyalty. Consumer Satisfaction partially positive and significant effect on Consumer Loyalty. Keywords: Brand Image, Product Quality, Consumer Satisfaction, Consumer Loyalty.